16=(x+3)(x-3)

Rewrite the equation as (x+3)(x-3)=16.

(x+3)(x-3)=16

Expand (x+3)(x-3) using the FOIL Method.

Apply the distributive property.

x(x-3)+3(x-3)=16

Apply the distributive property.

x⋅x+x⋅-3+3(x-3)=16

Apply the distributive property.

x⋅x+x⋅-3+3x+3⋅-3=16

x⋅x+x⋅-3+3x+3⋅-3=16

Simplify terms.

Combine the opposite terms in x⋅x+x⋅-3+3x+3⋅-3.

Reorder the factors in the terms x⋅-3 and 3x.

x⋅x-3x+3x+3⋅-3=16

Add -3x and 3x.

x⋅x+0+3⋅-3=16

Add x⋅x and 0.

x⋅x+3⋅-3=16

x⋅x+3⋅-3=16

Simplify each term.

Multiply x by x.

x2+3⋅-3=16

Multiply 3 by -3.

x2-9=16

x2-9=16

x2-9=16

x2-9=16

Add 9 to both sides of the equation.

x2=16+9

Add 16 and 9.

x2=25

x2=25

Take the square root of both sides of the equation to eliminate the exponent on the left side.

x=±25

Simplify the right side of the equation.

Rewrite 25 as 52.

x=±52

Pull terms out from under the radical, assuming positive real numbers.

x=±5

x=±5

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

x=5

Next, use the negative value of the ± to find the second solution.

x=-5

The complete solution is the result of both the positive and negative portions of the solution.

x=5,-5

x=5,-5

x=5,-5

Solve using the Square Root Property 16=(x+3)(x-3)